1985
DOI: 10.1111/j.1476-5381.1985.tb08943.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ablations in the central nervous system on arrhythmias induced by coronary occlusion in the rat

Abstract: 1 The role of the central nervous system (CNS) in arrhythmogenesis in the 4 h period following occlusion of a coronary artery was investigated in rats by use of CNS ablations and other procedures. 2 Ablations in the CNS included pithing, spinalization and decerebration combined with acute and chronic surgical preparation and noradrenaline/adrenaline infusions. 3 All procedures involving acute surgery reduced the incidence and severity of the arrhythmias induced by occlusion. Such reductions were most marked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…In addition, the reported antiarrhythmic actions of a-adrenoceptor antagonists in rat isolated ischaemic hearts was not attributed to xadrenoceptor antagonism (Daugherty & Woodward, 1982), rather to 'membrane stabilizing' effects of the drugs studies (Bralet et al, 1985). Finally, we have shown that in rats, neither combined a-and P-adrenoceptor blockade nor sympathectomy reduced arrhythmias (Botting et al, 1983), while graded ablations in the CNS and catecholamine infusions did not influence arrhythmias in a manner consistent with a role for a-(or P-)adrenoceptors in arrhythmogenesis during acute myocardial ischaemia (Curtis et al, 1985c). Therefore we consider it highly improbable that verapamil reduced ischaemia-induced arrhythmias in conscious rats via myocardial a-adrenoceptor antagonism.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the reported antiarrhythmic actions of a-adrenoceptor antagonists in rat isolated ischaemic hearts was not attributed to xadrenoceptor antagonism (Daugherty & Woodward, 1982), rather to 'membrane stabilizing' effects of the drugs studies (Bralet et al, 1985). Finally, we have shown that in rats, neither combined a-and P-adrenoceptor blockade nor sympathectomy reduced arrhythmias (Botting et al, 1983), while graded ablations in the CNS and catecholamine infusions did not influence arrhythmias in a manner consistent with a role for a-(or P-)adrenoceptors in arrhythmogenesis during acute myocardial ischaemia (Curtis et al, 1985c). Therefore we consider it highly improbable that verapamil reduced ischaemia-induced arrhythmias in conscious rats via myocardial a-adrenoceptor antagonism.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the absence of a significant difference in cardiac NE between 3-month-old and 14-month-old SHR ( Figure 3) is not contiguous with the marked difference in ventricular arrhythmias incidence existing between these two groups. Furthermore, it has been reported that catecholamines are not necessary mediators in early ischemic ventricular arrhythmias in the rat [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…We used halothane-anaesthetized rats in a previous study and conscious rats in this one. Pithed rats have high serum levels of potassium ion (Curtis et al, 1985), very low blood pressures due to the absence of sympathetic nervous activity, low cardiac output and supranormal responsiveness to catecholamines (Curtis & Walker, personal communication).…”
Section: Discussionmentioning
confidence: 99%